1977
DOI: 10.1002/jnr.490030203
|View full text |Cite
|
Sign up to set email alerts
|

Neurochemical effects of cocaine following acute and repeated injection

Abstract: Following repeated injection in the rat, cocaine decreased the concentration of serotonin in the septum-caudate and increased the metabolism of hypothalamic norepinephrine and also striatal dopamine to a lesser extent. Furthermore, cocaine significantly decreased the activity of the rate-limiting enzyme, tryptophan hydroxylase. In a comparative study d-amphetamine and methylphenidate were found to exert an effect opposite to cocaine in the activation of tryptophan hydroxylase. These findings indicate that coca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

1987
1987
2002
2002

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(25 citation statements)
references
References 17 publications
2
23
0
Order By: Relevance
“…Hyperactivity is one of the striking effects of cocaine in doses that generate moderate plasma levels, on the order of 2 M (Taylor and Ho, 1977;Benowitz, 1993). Blockade of this effect by a modified BChE is consistent with other evidence that sequestration or metabolic conversion of circulating cocaine lessens behavioral effects in rodents (Baird et al, 2000;Mets et al, 1998).…”
Section: Discussionsupporting
confidence: 84%
“…Hyperactivity is one of the striking effects of cocaine in doses that generate moderate plasma levels, on the order of 2 M (Taylor and Ho, 1977;Benowitz, 1993). Blockade of this effect by a modified BChE is consistent with other evidence that sequestration or metabolic conversion of circulating cocaine lessens behavioral effects in rodents (Baird et al, 2000;Mets et al, 1998).…”
Section: Discussionsupporting
confidence: 84%
“…In fact, even though antiserotoninergic properties have been attributed to co caine [18][19][20][21], some authors suggested that cocaine di rectly activates scrotoninergic receptors at the post-synaptic level [20],…”
Section: Discussionmentioning
confidence: 99%
“…Some authors reported that tissular levels of DA and its metabolites measured in the striatum were not affected in the short term after multiple injections of cocaine (Hanson et al, 1987;Taylor and Ho, 1977). On the other hand, Karoum et al (1990) reported a decrease in DOPAC without change in DA and HVA in the striatum, while in the nucleus accumbens, both DA and DOPAC were decreased immediately after chronic cocaine administration.…”
Section: Discussionmentioning
confidence: 92%